2022
DOI: 10.1017/sjp.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Version of the Generic Conspiracist Beliefs Scale

Abstract: Theorists acknowledge that conspiracy beliefs represent an established psychological construct. The study of conspiracy beliefs is important because allied ideation potentially influences everyday attitudes and behaviors across a range of domains (i.e., cognitive, social, cross-cultural, and political psychology). In this article, we analyze the internal structure and construct validity of the Spanish adaptation of the Generic Conspiracist Beliefs Scale (GCBS). Correlational and confirmatory factor analyses us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Despite the potential value of research into EUB, in Spain there is the obstacle of having very few EUB validated scales: to the best of our knowledge, there is only the Spanish adaptation of the Revised Paranormal Belief Scale (RPBS‐Sp; Díaz‐Vilela & Álvarez‐González, 2004), the Pseudoscientific Belief Scale (PSEUDO‐RS; Fasce et al, 2021), the Pseudoscience Endorsement Scale (PES; Torres et al, 2020), the UFO Experiences Questionnaire (UFO‐Q; Escolà‐Gascón et al, 2021), some subscales of the Spanish adaptation of the Expressions of Spirituality Inventory (ESI‐Sp; Muñoz‐García, 2013), and the Spanish adaptation of the Generic Conspiracist Beliefs Scale (GCBS‐Sp; Fasce et al, 2022). Despite the great advance brought by the existing psychometric instruments, there are some limitations that should be noted.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential value of research into EUB, in Spain there is the obstacle of having very few EUB validated scales: to the best of our knowledge, there is only the Spanish adaptation of the Revised Paranormal Belief Scale (RPBS‐Sp; Díaz‐Vilela & Álvarez‐González, 2004), the Pseudoscientific Belief Scale (PSEUDO‐RS; Fasce et al, 2021), the Pseudoscience Endorsement Scale (PES; Torres et al, 2020), the UFO Experiences Questionnaire (UFO‐Q; Escolà‐Gascón et al, 2021), some subscales of the Spanish adaptation of the Expressions of Spirituality Inventory (ESI‐Sp; Muñoz‐García, 2013), and the Spanish adaptation of the Generic Conspiracist Beliefs Scale (GCBS‐Sp; Fasce et al, 2022). Despite the great advance brought by the existing psychometric instruments, there are some limitations that should be noted.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Serbian adaptation of the GCBS provided gender non‐biased scores and performed well in comparison to the English language version. Overall, results indicated that the GCBS was a suitable measure for cross‐societal and cross‐national comparisons (Fasce et al, 2022; Siwiak et al, 2019). Furthermore, the findings of this study support the notion that most aspects of conspiracy beliefs are more present in societies characterised by a long history of ongoing international conflicts and wars.…”
Section: Discussionmentioning
confidence: 99%
“…This process has sometimes yielded different factorial solutions. Therefore, while the correlated five‐factor GCBS structure has been successfully reproduced with samples from Poland (Siwiak et al, 2019) and Spain (Fasce et al, 2022), other studies have proposed alternative solutions (e.g., Atari et al, 2019; Swami et al, 2017).…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite reporting a superior model fit for the correlated five-factor model (vs. one-factor solution), Brotherton and French ( 2014 ) recommended using the total score because it captures a coherent set of allied beliefs that best reflect assumptions about the typicality of conspiratorial activity. While several studies have reproduced the correlated five-factor model (i.e., Siwiak et al, 2020 ; Fasce et al, 2022 ), others have reported alternative solutions and found a poor fit for a single-factor solution (e.g., Swami et al, 2017 ; Atari et al, 2019 ; Majima and Nakamura, 2020 ).…”
Section: Introductionmentioning
confidence: 99%